Infrastructure Reform, Better Subsidies, and the Information Deficit - Gómez-Lobo, Andrés; Foster, Vivien; Halpern, Jonathan (World Bank, Washington, DC, 2012)
In developing countries the provision of water and sanitation services is often subsidized. These subsidies take the form of a general underpricing of water, numerous cross-subsidies, and inefficient billing and collection. An essential part of infrastructure reform is the redesign of subsidies. In the design of an optimal subsidy scheme the key decisions are the choice of eligibility criteria, the level of the subsidy and the budgetary requirements. However, the lack of consistent and reliable data sets which combine socioeconomic and water consumption information may be an important obstacle to making good decisions, undermining efforts to provide affordable water services for the poor. This Note discusses the type of information required, where it can be found, and ways to deal with shortcomings in the data. To illustrate, the Note draws on data from World Bank work in Panama.